KONSEP MODEL KEPERAWATAN BERDASARKAN SELF TRANSCENDENCE THEORY PAMELA G. REED - Cornellia Moningka; Irna Nursanti (Nusantara Hasana Journal, 2024)
The world of nursing is currently increasingly developing. Considered as a health profession, nurses must participate in achieving health development goals both in Indonesia and throughout the world. Self-transcendence theory is built on the assumption that humans have an inner capacity, their own inner care process to integrate the complexities of life in a way that facilitates well-being during the face of health-related problems. The strengths of Pamela G Reed's theory are: This theory is very appropriate to use in the assessment process because the variables used cover the phenomena that occur; Good for solving various problems related to psychosocial problems; Spiritual factors are widely considered in solving client problems. Weaknesses of Pamela G Reed's Theory, namely: Some charts do not have a clear summary linking the variables; Many theoretical variables, such as sensitivity and self-transcendence, as well as conditions of well-being, are still abstract, making them difficult to apply in practice; The theoretical discussion is difficult to understand so it is difficult for nurses to apply it into practice; It is limited to use only in cases related to psychological problems and does not consider physical treatment.